"I swear it is Tourette's!": On functional coprolalia and other tic-like vocalizations. (30th December 2016) - Ganos, Christos; Edwards, Mark J.; Müller-Vahl, Kirsten
Abstract: Coprolalia in neuropsychiatry is typically associated with tic disorders, in particular Gilles de la Tourette syndrome. To date, there has been no report of functional coprolalia. Here, we provide the clinical characteristics of 13 adolescent and adult patients with coprolalic and other functional tic-like complex vocalizations who, on the basis of these symptoms, were misdiagnosed with a primary tic disorder, most commonly Gilles de la Tourette syndrome. We describe similarities and highlight the differences from primary tic disorders in order to provide a pragmatic list of clinical clues that will facilitate correct diagnostic labeling and thereby treatment. Finally, we emphasize that the distinction between a primary and a functional tic disorder should rely on a combination of neuropsychiatric symptoms and signs and not on the presence of single, however striking, abnormal behaviors, such as coprolalia. Highlights: Coprolalia is commonly associated with Gilles de la Tourette syndrome. Functional coprolalia has not been previously described. We describe 13 patients with functional vocalizations, including coprolalia. Clinical clues are provided to aid the distinction of functional from primary tics.